2017
DOI: 10.1038/nature23010
|View full text |Cite
|
Sign up to set email alerts
|

Open and closed structures reveal allostery and pliability in the HIV-1 envelope spike

Abstract: SUMMARY For many enveloped viruses, binding to a receptor(s) on a host cell acts as a first step in a series of events culminating in fusion with the host cell membrane and transfer of genetic material for replication [for review see1,2]. The envelope glycoprotein (Env) trimer on the surface of HIV is responsible for receptor binding and fusion. While Env can tolerate a high degree of mutation in five variable regions (V1-V5), and also at N-linked glycosylation sites that contribute roughly half the mass of En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
466
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(517 citation statements)
references
References 54 publications
34
466
2
1
Order By: Relevance
“…We and others have shown that soluble CD4 induces a metastable conformation of the trimer in which gp120 protomers are displaced but still remain involved in the gp41 interaction thus incapable of exposure of the A32- and C11-epitope regions (Acharya et al, 2014; Ozorowski et al, 2017; Pancera et al, 2010; Wang et al, 2016). We are able, however, to induce the conformational changes of the viral trimer similar to those induced by cell surface CD4 with the CD4 miniprotein mimetic M48U1 alone or in combination with co-receptor binding site antibody.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We and others have shown that soluble CD4 induces a metastable conformation of the trimer in which gp120 protomers are displaced but still remain involved in the gp41 interaction thus incapable of exposure of the A32- and C11-epitope regions (Acharya et al, 2014; Ozorowski et al, 2017; Pancera et al, 2010; Wang et al, 2016). We are able, however, to induce the conformational changes of the viral trimer similar to those induced by cell surface CD4 with the CD4 miniprotein mimetic M48U1 alone or in combination with co-receptor binding site antibody.…”
Section: Discussionmentioning
confidence: 97%
“…In the pre-fusion trimer, the N- and C- termini of gp120 are held by a triple-tryptophan clasp consisting of tryptophans 623, 628, and 623 of gp41 (Pancera et al, 2014). Upon binding of the Env trimer to the cell surface CD4, the inner domain of gp120 undergoes a series of conformation rearrangements with the formation of the bridging sheet and changes to the region of the nascent N5-i5 epitope (conformation from PDB: 5VN3, (Ozorowski et al, 2017)). In this state, the α0-helix and the -strand of the N5-i5 epitope are formed and the β1 helix is positioned to assume conformation as seen in the N5-i5-bound state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, cryo‐electron microscopy (CryoEM)—emerging as the new powerful structural technique of the moment—is already transforming the way we look into complex biological macromolecules . In this respect, Ozorowski et al . studied the open and closed structures of HIV‐1 envelope glycoprotein (gp120; Env) to reveal allosteric control mechanisms, raising the possibility of using this knowledge for the design of HIV‐1 inhibitors.…”
Section: Modulating Protein Functions With Allosteric Chemical Switchesmentioning
confidence: 99%
“…Twenty antibody classes targeting six epitopes on the prefusion closed HIV-1 Env trimer have been characterized using SPA (Table 3) and crystallographic studies (Chuang et al 2019). 'Breathing' by HIV-1 B41 SOSIP.664 trimers was found to expose the b12 epitope (Ozorowski et al 2017), and a similar motion by influenza HA protomers was also revealed by SPA (Turner et al 2019). S230 binding induces fusogenic conformational rearrangements in the SARS-CoV S glycoprotein, while the MERS-CoV S glycoprotein remains its prefusion conformation upon LCA60 binding Walls et al 2019).…”
Section: Enveloped Viruses Without Icosahedral Symmetrymentioning
confidence: 80%